Globalization, structural adjustment and security : the collapse of the post-colonial developmental state in the Caribbean - Thomas, Clive Y. (1998)
Posits that the 'developmental state' which had emerged in the Caribbean after independence - with in some instances e.g. Guyana and Grenada, its own distinctive blend of authoritarianism, nationalism, and populism - has collapsed under the twin pressures of U.S. self-defined geo-strategic national interest in the area and globalization. Suggests that in the wake of this collapse a state crafted along neo-liberal lines and driven by neo-liberal ideology is being recomposed.